Kobiety wśród wolnych zawodów w Polsce - Antkowiak, Paweł (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2010)
Od pewnego czasu w Polsce trwa dyskusja na temat sytuacji kobiet w życiu społeczno-politycznym. Mimo szeroko deklarowanej równości w sferze zatrudnienia występują wyraźne dysproporcje. Po przemianach demokratycznych z roku 1989 funkcjonuje w Polsce kilkanaście profesji, które powszechnie uznawane są za tzw. wolne zawody. Część z nich zorganizowana jest w ramach samorządu zawodowego. Przedmiotem tego opracowania jest sytuacja kobiet w ramach tzw. wolnych zawodów oraz w strukturach samorządu zawodowego w Polsce.

For some time in Poland there is a discussion about the situation of women in social and political life. Although widely declared equality in employment disparities exist. After the democratic changes in 1989 in Poland there are several professions that are called liberal professions. Some of them are organized in a professional self-government. The subject of this paper is the situation of women in liberal professions and professional self-government structures in Poland.
Women among the Liberal Professions in Poland
Keywords: Kobiety; Wolne zawody; Samorząd zawodowy; Women; Liberal professions; Professional self-government